Influence of diet, exercise, and dietician's on the incidence and survival of japanese dialysis patients - Satoshi Ogata; Kenji Wakai; Kunitoshi Iseki; Yoshiharu Tsubakihara (The Korean Society of Nephrology, 2012)
It is known that there are distinct regional differences in the incidence and prevalence of dialysis, as well as the survival of dialysis patients in Japan. We investigated the relationship between diet, the level of exercise, and the incidence of dialysis due to diabetes mellitus (DM) and chronic glomerulonephritis (CGN). We also investigated the influence of access to full-time and part-time dieticians at dialysis centers on survival. We used data for the 47 prefectures of Japan from the National Nutrition Survey 1995-99 (n=38,003) and the Japanese Society for Dialysis Therapy 2005-07 (n=45,033). The impact of each factor was assessed by univariate regression analysis. Univariate analysis showed that body mass index (BMI) (r=0.296, p=0.022), intake of fish and shellfish (r=−0.254, p=0.043), and the intake of meat (r=0.275, p=0.031) were correlated with the incidence of new patients starting dialysis due to DM. In addition, the BMI (r=0.355, p=0.014), number of steps walked daily (r=−0.358, p=0.014), intake of green and yellow vegetables (r=−0.424, p=0.003), intake of fish and shellfish (r=−0.358, p=0.014), and intake of milk (r=−0.529, p<0.001) were correlated with the incidence of new patients starting dialysis due to CGN. Access to full-time dieticians was correlated with the 1-year survival of new dialysis patients (r=0.294, p=0.023), but not access to part-time dieticians. We conclude that nutritional advice might play an important role in survival in dialysis patients.